Syphilis with Recent phase papullomatous: typical clinic, wrong diagnosis - Gardioli, Daniela D.S.; Gouvea, Tegnus V.D.; Nascimento, Auri V.S.; Faria, Priscilla F.M.; Silva, Ivo A.; Silva, José C.S.; Firmo, Flávia H.C. (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Syphilis is a chronic infectious disease that is critical when not treated or treated inadequately. It is unacceptable that 50 years after its clinical evolution and minute description, featuring simple evidentiary laboratory tests to be performed, inexpensive and available in primary health care, syphilis diagnosis continues to present difficulties. This paper aims to report a case of recent syphilis in papullomatous phasein an user of the Health System who was not diagnosed despite pathognomonic clinical and laboratory examination proving. We conclude that the unpreparedness of some health professionals from public primary care constitutes an important parameter to be evaluated in order to implement effective actions to control this sexually transmitted disease.